2020
DOI: 10.1021/acs.jmedchem.0c00193
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of Quinazolin-4-one-Based Hydroxamic Acids as Dual PI3K/HDAC Inhibitors

Abstract: A series of quinazolin-4-one based hydroxamic acids was rationally designed and synthesized as novel dual PI3K/HDAC inhibitors by incorporating an HDAC pharmacophore into a PI3K inhibitor (Idelalisib) via an optimized linker. Several of these dual inhibitors were highly potent (IC 50 < 10 nM) and selective against PI3Kγ, δ and HDAC6 enzymes and exhibited good antiproliferative activity against multiple cancer cell lines. The lead compound 48c, induced necrosis in several mutant and FLT3-resistant AML cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 69 publications
(129 reference statements)
0
45
0
Order By: Relevance
“…The limited clinical efficacy of PI3K inhibitors promotes the development of combinational therapies or chimeric PI3K MTDs. Thakur et al developed a series of chimeras by incorporating HDAC ZBG into the solvent-exposed region of PI3K inhibitor idelalisib [113]. The linker part was systematically explored, and compound 49 with a phenylhydroxamate motif maintained a high potency against PI3Kγ and PI3Kδ with IC 50 values of 9.0 and 7.0 nM, respectively.…”
Section: Nonhydroxamate Acid-derived Inhibitorsmentioning
confidence: 99%
“…The limited clinical efficacy of PI3K inhibitors promotes the development of combinational therapies or chimeric PI3K MTDs. Thakur et al developed a series of chimeras by incorporating HDAC ZBG into the solvent-exposed region of PI3K inhibitor idelalisib [113]. The linker part was systematically explored, and compound 49 with a phenylhydroxamate motif maintained a high potency against PI3Kγ and PI3Kδ with IC 50 values of 9.0 and 7.0 nM, respectively.…”
Section: Nonhydroxamate Acid-derived Inhibitorsmentioning
confidence: 99%
“…To design HDAC and PI3K inhibitors with a better toxicity profile and a wider therapeutic window, Thakur and colleagues proposed the selective inhibition of specific isoforms of HDAC and PI3K [119] . The PI3K/HDAC dual inhibitors were designed by analyzing the crystal structures of idelalisib ( 5 ) in PI3Kδ [120] and vorinostat ( 1 ) in HDAC2 [92] .…”
Section: Exploring Selectivity In Multitarget Hdac and Pi3k Inhibitorsmentioning
confidence: 99%
“…The PI3Kα is widely expressed in the body and also is related with the insulin signaling pathway and is related with the hyperglycemia [29,30,32] . They observed that the carbonyl and fluoro group in the quinazolinone extended into the solvent exposed region and enabled the introduction of the HDAC pharmacophore (linker and zinc binding group) [119] (Figure 11). From the SAR studies, several compounds acted as potent and selective PI3Kδ/PI3Kγ/HDAC6 inhibitors with good cellular potencies against a panel of 60 different cancer cell lines.…”
Section: Exploring Selectivity In Multitarget Hdac and Pi3k Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations